The mediating role of eco-innovation between adaptive environmental strategy, absorptive capacity, and environmental performance (2024)
This article delves into the role of adaptive environmental strategies, absorptive capacity, and eco-innovation in enhancing environmental performance, particularly in the context of market turbulence. The study, conducted among 568 companies in Colombia, employs structural equation modeling to evaluate relationships between the studied variables. The findings suggest that adaptive strategies alone do not directly impact environmental performance, emphasizing the need for integration with eco-innovation initiatives. Moreover, organizations with high absorptive capacity can leverage market turbulence to drive eco-innovative initiatives, highlighting the indirect yet significant impact of market turbulence on environmental performance through absorptive capacity. The study underscores the critical role of eco-innovation in directly influencing environmental outcomes, suggesting that the effectiveness of adaptive strategies and absorptive capacities hinges on successful eco-innovation initiatives. These insights offer practical guidance for organizations seeking to enhance their environmental performance in turbulent markets, providing a roadmap for sustainable business practices.